Termin kandaulos/kandylos (κανδαυλοσ/ κανδυλοσ) na podstawie λεχεων συναγωγη Focjusza oraz "Commentari ad Homeri Iliadem" Eustacjusza z Tessaloniki - Kokoszko, Maciej; Gibel-Buszewska, Katarzyna (Vox Patrum, 2010)
The present article focuses on one of the Greek delicacies mentioned by Photius and Eustathius, i.e. a Lydian import called kandaulos/kandylos. The dish was developed before the mid. VI th c. BC and named after a Lydian king, Kandaules, who ruled in the VII th c. BC. The delicacy was (via the Ionians) borrowed by the Helens and established itself in Greece sometime in the V th c. It became popular in Hellenistic times. The information we possess allow us to reconstruct two varieties of kandaulos/ kandylos. The first was savoury and consisted of cooked meat, stock, Phrygian cheese, breadcrumbs and dill (or fennel). The other included milk, lard, cheese and honey. The dish is reported to have been costly, prestigious and indicating the social status of those who would eat it. Though there is much evidence suggesting its popularity in antiquity, we lack solid evidence proving that kaunaudlos/kandylos was eaten in Byzantine times. On the other hand, Byzantine authors preserved the most detailed literary data on the delicacy. If it had not been for the Byzantine interest, our competence in the field of Greek cuisine would be even faultier.